(Un)believing in modern society: religion, spirituality, and religious-secular competition - Stolz, Jörg (Routledge, 2016)
1. Introduction : religion and spirituality in the me-society -- 2. A theory of religious-secular competition -- 3. Four forms of (un)belief -- 4. Identity and social structure -- 5. Belief, knowledge, experience, action -- 6. Values and change of values -- 7. Major churches, Evangelical churches and alternative-spiritual suppliers -- 8. The perception and evaluation of religion(s) -- 9. The change in religiosity, spirituality and secularity -- 10. Conclusion : (un)believing in modern society.